Children and young people's participation in disaster risk reduction : agency and resilience - Mort, Maggie; Rodriguez-Giralt, Israel; Delicado, Ana (Policy Press, 2020)
Available Open Access under CC-BY-NC licence. Disasters are an increasingly common and complex combination of environmental, social and cultural factors. Yet existing response frameworks and emergency plans tend to homogenise affected populations as 'victims', overlooking the distinctive experience, capacities and skills of children and young people. Drawing on participatory research with more than 550 children internationally, this book argues for a radical transformation in children's roles and voices in disasters. It shows practitioners, policy-makers and researchers how more child-centred disaster management, that recognises children's capacity to enhance disaster resilience, actually benefits at-risk communities as a whole.